Pengaruh Emotional Intelligence dan Organizational Culture terhadap Organizational Citizenship Behavior pada Karyawan RSUD Sidoarjo Barat - Najwa Meita Kurnia; Khoirur Rozaq (Jurnal Ilmu Manajemen, 2025)
This study investigates the relationship between emotional intelligence, organizational culture, and organizational citizenship behavior (OCB) among management employees in a type C hospital established in 2021. Using a quantitative approach, the research applied a saturated sampling technique involving 55 respondents. Data were analyzed with Structural Equation Modeling (SEM) through SmartPLS 4.0.9.9 to test the proposed hypotheses. The findings indicate that emotional intelligence has a positive and significant effect on OCB, suggesting that employees with higher emotional intelligence tend to demonstrate stronger discretionary behaviors that benefit the organization. Similarly, organizational culture also shows a positive and significant effect on OCB, highlighting the role of shared values and norms in encouraging supportive behaviors among employees. However, the moderating effect of organizational culture on the relationship between emotional intelligence and OCB was not supported in this study. From a managerial perspective, the results provide practical implications: management should focus on developing programs to enhance employees’ emotional intelligence and foster a strong organizational culture. These efforts are essential to sustain positive behaviors beyond formal job descriptions, ultimately contributing to improved organizational effectiveness and service quality.